Automated solvent system screening for the preparative countercurrent chromatography of pharmaceutical discovery compounds. Issue 23 (2nd December 2015) - Bradow, James; Riley, Frank; Philippe, Laurence; Yan, Qi; Schuff, Brandon; Harris, Guy H.
Abstract : A fully automated countercurrent chromatography system has been constructed to rapidly screen the commonly used heptane/ethyl acetate/methanol/water solvent system series and translate the results to preparative scale separations. The system utilizes "on‐demand" preparation of the heptane/ethyl acetate/methanol/water solvent system upper and lower phases. Elution‐extrusion countercurrent chromatography was combined with non‐dynamic equilibrium injection reducing the screening time for each heptane/ethyl acetate/methanol/water system to 17 min. The result enabled solvent system development to be reduced to under 2 h. The countercurrent chromatography system was interfaced with a mass spectrometer to allow selective detection of target components in crude medicinal chemistry reaction mixtures. Mass‐directed preparative countercurrent chromatography purification was demonstrated for the first time using a synthetic tetrazole epoxide derived from a routine medicinal chemistry support workflow.